(untitled) (African Journal of Biomedical Research, 2020)
Diabetes is now becoming a major public health problem globally. It is increasingly associated with renal diseases, particularly chronic kidney disease worldwide. A simple, accurate, reproducible and non-invasive method of evaluation is necessary for early morphological assessment for timely intervention, diagnosis, treatment, and evaluation of renal diseases in diabetes mellitus. In this cross-sectional comparative study, among one hundred and four adult diabetic cases and fifty-three healthy controls, the ultrasonographic renal dimensions were determined and compared in both cases and controls. Correlations were sought between the renal dimensions and the clinical, anthropometric, and metabolic characteristics of the study population. The dimensions of the kidneys in diabetic cases versus controls were; lengths (9.94± 0.76cm vs 9.27 ± 0.90 and 10.28 ± 0.87cm vs 9.41± 1.02cm(p=<0.001), cortical thickness (1.77± 0.28cm vs 1.26± 0.49cm, p<0.001 and 1.89± 0.52cm vs 1.37± 0.78cm, p<0.001 and volumes (121.9± 39.50cm3 vs 107.8± 29.82cm, p=0.026 and 136.3± 45.09cm3 vs 118.8± 33.79cm3, (p=0.015) were significantly higher in Diabetes mellitus cases on the right and left respectively. The waist circumference, fasting blood sugar, postprandial blood sugar, cholesterol, and urinary albumin, all had correlations with the mean kidney length. Taking together, the ultrasonographic renal lengths, cortical thickness, and volumes are increased in diabetic disease without renal function compromise compared to age-, gender- and body mass index-matched non-diabetic controls. The clinical, anthropometric, and metabolic parameters of the diabetes cases also showed significant correlations with mean kidney length